The Effect of Cardio Tennis Exercises on Lipid Metabolism of Sedentary Women - Karagöz, Şeniz; Ünveren , Alparslan; Köken, Tülay (Progress in Nutrition, 2020)
Background: It is known that regularly done exercises have physical, physiological, social and spiritual effects on people. In this currently performed study, it was intended to investigate the effect of regular cardio tennis exercises on lipid metabolism of middle-aged sedentary women. Methods: The sample group of this study is consisted of 30 healthy middle-aged sedentary women with a mean age of 44.40 ± 3.89. Body components of exercise group subjects were analyzed by bioelectrical impedance analyzer before the program, during mid-program (in the 5th week) and after the program (in the 10th week) and their blood samples were taken so as to determine the lipid metabolism of exercise group subjects. To fulfill this aim, depending on cardio tennis exercises carried out for 10 weeks, three days a week for one hour; body components, total cholesterol, triglyceride, LDL-cholesterol, HDL-cholesterol, changes in the leptin and ghrelin hormone levels of middle age sedentary women have been examined. Results: As a result of the findings obtained in the research, it was identified that HDL cholesterol levels of sedentary women who participated in the study have shown a statistically significant increase after 10 weeks (p 0.05). Conclusion: Consequently, it was concluded that regularly performed cardio tennis exercises had a positive effect on body components of sedentary women while it only increased HDL-cholesterol lipid, which is included in the metabolism parameters.